2018
DOI: 10.1111/jgs.15508
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Antidepressant Use and Risk of Dementia in a Prospective Cohort Study

Abstract: Most commonly prescribed nonanticholinergic depression medications used in late life do not appear to be associated with dementia risk. Paroxetine and other anticholinergic antidepressants may be exceptions in older individuals. Future studies are warranted to improve scientific understanding of potential associations in other settings and populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 43 publications
(112 reference statements)
3
19
0
Order By: Relevance
“…The chronic use of anticholinergic antidepressants might contribute to this pathogenic transformation [318]. It is also well-known that over 60% of patients chronically treated with antipsychotics develop extrapyramidal symptoms which may induce severe motor disability [319]. Over 80% of nursing home residents are daily consumers of psychotropic drugs [320,321] which are prescribed in excessive doses, for excessive duration, and without adequate monitoring and/or indications for their use [322].…”
Section: Further Considerationsmentioning
confidence: 99%
“…The chronic use of anticholinergic antidepressants might contribute to this pathogenic transformation [318]. It is also well-known that over 60% of patients chronically treated with antipsychotics develop extrapyramidal symptoms which may induce severe motor disability [319]. Over 80% of nursing home residents are daily consumers of psychotropic drugs [320,321] which are prescribed in excessive doses, for excessive duration, and without adequate monitoring and/or indications for their use [322].…”
Section: Further Considerationsmentioning
confidence: 99%
“…In a cohort study excluding antidepressant exposure in the years preceding dementia diagnosis, cumulative use of most antidepressants was not associated with later dementia, except for paroxetine, which increased its risk. 20 Taking a lag time into account, we found no association. The stratification according to treatment duration did not allow us to identify any association, whatever the treatment duration, that is 3 months or less or more than 3 months compared with no dispensing.…”
Section: Discussionmentioning
confidence: 64%
“…Studies that did not assess for history or severity of depression prior to inclusion yielded contradictory results [58]. One study found paroxetine is associated with a higher risk of developing AD compared to other SSRIs or no use [65]. Paroxetine's anticholinergic action could increase the risk of cognitive effects in vulnerable populations.…”
Section: Limitations Of the Existing Evidence In Admentioning
confidence: 99%